High Coverage of Antiretroviral Treatment With Annual Home-Based HIV Testing, Follow-up Linkage Services, and Implementation of Test and Start: Findings From the Chókwè Health Demographic Surveillance System, Mozambique, 2014–2019. (1st April 2021) - Pathmanathan, Ishani; Nelson, Robert; de Louvado, Alzira; Thompson, Ricardo; Pals, Sherri; Casavant, Isabelle; Cardoso, Maria Judite Antonio; Ujamaa, Dawud; Bonzela, Juvêncio; Mikusova, Silvia; Chivurre, Victor; Tamele, Stelio; et al.
Abstract : Background: Early antiretroviral therapy (ART) is necessary for HIV epidemic control and depends on early diagnosis and successful linkage to care. Since 2014, annual household-based HIV testing and counseling and linkage services have been provided through the Chókwè Health and Demographic Surveillance System for residents testing HIV positive in this high HIV-burden district. Methods: District-wide Test and Start [T&S, ART for all people living with HIV (PLHIV)] began in August 2016, supported by systematic interventions to improve linkage to care and treatment. Annual rounds (R) of random household surveys were conducted to assess trends in population prevalence of ART use and viral load suppression (<1000 viral RNA copies/mL). Results: Between R1 (April 2014–April 2015) and R5 (April 2018–Mar 2019), 46, 090 (67.2%) of 68, 620 residents aged 15–59 years were tested for HIV at home at least once, and 3711 were newly diagnosed with HIV and provided linkage services. Population prevalence of current ART use among PLHIV increased from 65.0% to 87.5% between R1 and R5. ART population prevalence was lowest among men aged 25–34 years (67.8%) and women aged 15–24 (78.0%), and highest among women aged 35–44 years (93.6%) and 45–59 years (93.7%) in R5. Viral load suppression prevalence increased among all PLHIV aged 15–59 years from 52.0% in R1 to 78.3% in R5. Discussion: Between 2014 and 2019, Chókwè Health and Demographic Surveillance System residents surpassed the UNAIDS targets of ≥81% of PLHIV on ART and ≥73% virally suppressed. This achievement supports the combination of efforts from household-based HIV testing and counseling, support for linkage to care and treatment, and continued investments in T&S implementation.